Pleurectomy for persistent pain in benign asbestos-related pleural disease. Issue 2 (February 1995) - Fielding, D I; McKeon, J L; Oliver, W A; Matar, K; Brown, I G
Abstract : BACKGROUND--Persistent severe pain is a rare complication of benign asbestos-related pleural disease. METHODS--Four patients are described in whom pain persisted for more than one year (range 18 months to five years) which was incompletely relieved by opioid medication and nerve blocking procedures. All underwent pleurectomy in an attempt to relieve it. RESULTS--At operation the pleura was considerably thickened in all cases. Two of the four patients had successful relief of pain. The other two had a neuralgic component to their pain before surgery which persisted afterwards. One of these patients underwent successful cervical cordotomy. CONCLUSIONS--Pleurectomy may provide relief in patients with constant pleuritic pain due to benign asbestos-related pleural thickening. It seems, however, that patients in whom the pain has a neuralgic component are unlikely to benefit.